Compute the square root of ( 6 8 9 ) ( 6 9 0 ) ( 6 9 1 ) ( 6 9 2 ) + 1 without using a calculator.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
N = ( 6 8 9 ) ( 6 9 0 ) ( 6 9 1 ) ( 6 9 2 ) + 1 = ( a − 2 3 ) ( a − 2 1 ) ( a + 2 1 ) ( a + 2 3 ) + 1 = ( a 2 − 4 9 ) ( a 2 − 4 1 ) + 1 = a 4 − 2 5 a 2 + 1 6 2 5 = ( a 2 − 4 5 ) 2 = 4 7 6 7 8 9 2 Let a = 6 9 0 . 5
Therefore, N = 4 7 6 7 8 9 .
( m − 1 ) ( m ) ( m + 1 ) ( m + 2 ) + 1 = a 2
Take 1 to RHS and combine (1,4),(2,3) terms
( m 2 + m ) ( m 2 + m − 2 ) = ( a + 1 ) ( a − 1 )
Difference between the terms in LHS and RHS both is 2 . So we can conclude that :
( m 2 + m = a + 1 ) , ( m 2 + m − 2 = a − 1 )
In question, m = 6 9 0 and a is to be found
So, ( 6 9 0 ) 2 + 6 9 0 = a + 1
4 7 6 7 9 0 = a + 1 Or,
a = 4 7 6 7 8 9
( a − 2 ) ( a − 1 ) a ( a + 1 ) + 1 = ( a 2 − 2 a ) ( a 2 − 1 ) + 1 = a 4 − 2 a 3 − a 2 + 2 a + 1 = ( a 2 − a − 1 ) 2 . For a = 6 9 1 , the value of the square root of this expression is ( 6 9 1 2 ) − 6 9 1 − 1 = 4 7 6 7 8 9 .
Problem Loading...
Note Loading...
Set Loading...
x ( x + 1 ) ( x + 2 ) ( x + 3 ) + 1 = ( x 2 + 3 x ) ( x 2 + 3 x + 2 ) + 1 = ( x 2 + 3 x ) ( x 2 + 3 x + 1 ) + x 2 + 3 x + 1 = = ( x 2 + 3 x + 1 ) ( x 2 + 3 x + 1 ) = ( x 2 + 3 x + 1 ) 2 = ∣ ∣ x 2 + 3 x + 1 ∣ ∣ = x = 6 8 9 ∣ ∣ 6 8 9 2 + 3 ⋅ 6 8 9 + 1 ∣ ∣ = ∣ 4 7 4 7 2 1 + 2 0 6 7 + 1 ∣ = 4 7 6 7 8 9